Multiple-choice questions in assessment: Perceptions of medical students from low-resource setting - Venkata Avinash Kumar Vegi; P V Sudhakar; Devi Madhavi Bhimarasetty; Kiran Pamarthi; Lokesh Edara; L V Simhachalam Kutikuppala; Tarun Kumar Suvvari; Shubham Anand (Wolters Kluwer Medknow Publications, 2022)
BACKGROUND: In curriculum reforms under Competency-Based Medical Education (CBME) introduced by the National Medical Commission, medical students are recognized as one of the stake holders. The well-designed multiple-choice questions (MCQs) help students in assessment as well as promote deep learning. The objective of this study is to assess the perceptions of the Indian medical students towards the examination patterns in their undergraduate curriculum with particular reference to MCQs. MATERIALS AND METHODS: An observational cross-sectional study was conducted among the medical colleges in India. A total of 7875 students took part in the study. The study instrument was a validated pretested self-administered questionnaire. The study was conducted as an online survey using the Google Forms platform. Inclusion criteria were students from all professional years as well as interns and those who were willing to participate in the study. RESULTS: For the question of initiation of MCQs as a tool for the assessment, many of the students (46%) expressed that it should start from the 1st MBBS itself. The majority of the students (85%) felt that MCQ oriented preparation will be helpful for MBBS professional (theory and practical) examinations. Most of the students (90.9%) preferred that the MCQs should be concept and case scenario based. To the question of whether the current system of the university theory examinations of essays and short notes be replaced in total with MCQs so that they are more prepared for NEXT and USMLE examination, 65.5% responded with an answer of yes. CONCLUSION: The findings of this study provide input to the regulatory authorities and other stakeholders responsible for designing and implementing the medical curriculum.